(untitled) (Academicia Globe: Inderscience Research, 2022)
Atherosclerosis is a chronic disease around the world and is the main cause of death risk for patients with atherosclerosis and type 2 diabetes , the study aimed to evaluate the effect of vitamin D and lipid profile in patients with atherosclerosis, the study was conducted on patients referred to specialized clinics in Kirkuk and Cardiology Hospital in Sulaymaniyah for the period from August 2021 to January 2022, the study included sixty samples of men whose ages ranged between 40 and 70 years , distributed into three groups, the first included twenty men with atherosclerosis, the second group included twenty men with atherosclerosis and type II diabetes, and the third group included twenty healthy men with the same age range as the samples , the results of the current study showed a significant decrease of vitamin D in the groups affected by atherosclerosis and diabetes mellitus compared to the control group, and there was a clear increase in the lipid profile such as cholesterol, triglycerides, low-density lipoproteins and very low-density lipoproteins, atherogenic index , except for a decrease in the level of lipoproteins high density and this predicts the risk of atherosclerosis and diabetes, and is considered a diagnostic marker for atherosclerosis in patients.